Analisis Manejemen Laba Perusahaan Di Indonesia - Dwi Nur Fadillah; Maya Macia Sari; Khaela Febrianti; Nur Hafizah Fatimah (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
Research with the title "Analysis of earnings management in Indonesia" with a qualitative descriptive research method using secondary data taken from existing data sources and existing instruments. Here there is a discussion about how to analyze the development of earnings management in Indonesia and also the aim of this research is to prove and analyze the influence of earnings management in Indonesia for a company that must be registered on the IDX and there is also a basic concept of earnings management including an understanding of how a company can utilize the research methods provided to improve financial performance more flexibly by involving practices such as preparing reserves, determining methods that influence profits and involving the consequences of weaknesses or risks that exist in these profits.